Streptooctatins A and B, fusicoccane-type diterpenoids with autophagic activity from Streptomyces sp. KCB17JA11. (1st February 2022) - Jang, Jun-Pil; Jang, Mina; Hwang, Gwi Ja; Kim, Min Hee; Ahn, Jong Seog; Ko, Sung-Kyun; Jang, Jae-Hyuk
Graphical abstract: Abstract: Two new fusicoccane-type diterpenoids, streptooctatins A (1 ) and B (2 ), together with a known compound cyclooctatin (3 ) were isolated from Streptomyces sp. KCB17JA11. The structures of 1 and 2 were determined by analyzing spectroscopic and spectrometric data from 1D and 2D NMR and HRESIMS experiments. Compounds 1 and 2 induced EGFP-LC3 puncta indicating autophagic activities against HeLa cells without cytotoxicity.